Development of antipodal Vivaldi antenna for microwave brain stroke imaging system - Salleh, Azahari; Chiou Yang, Ching; Singh Jit Singh, Mandeep; Tariqul Islam, Mohammad (International Journal of Engineering and Technology, 2019)
In recent years, Microwave Imaging (MWI) has offered an effective solution in medical applications, especially in detecting abnormal body tissues in the human brain. Among the popular detection methods currently being used in hospitals are Magnetic Resonance Imaging (MRI) and Computed Tomography (CT) scans. But the constraints faced by this method include the high cost of equipment and its large size and static nature. In this article, the antipodal Vivaldi antenna for the microwave brain stroke imaging system is designed and presented. Nine antipodal Vivaldi antennas were proposed and designed using Computer Simulation Technology (CST) software operating from 2.06 GHz to 2.61 GHz. A Radio Frequency (RF) switch was used to enable the antenna sequentially received the backscattered signal from the head phantom. Then, MATLAB software was used to interface between the Python algorithm and the Vector Network Analyzer (VNA) for the purpose of data collection. The Python algorithm was able to control the rotation of the platform, which rotated in 50 positions. The fabricated antennas are based on a Rogers RO4350B substrate and show good agreement between the measured result and simulated result. The designed antennas were able to achieve 86.92% average efficiency, 2.45 dBi gain and stable radiation directivity. Finally, from the variation of the color in color plot, a target structure was successfully detected.Â Â